1993
DOI: 10.1161/01.atv.13.12.1865
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the hemostatic system in the insulin resistance syndrome. A study of 1500 patients with angina pectoris. The ECAT Angina Pectoris Study Group.

Abstract: a major indicator of insulin resistance, may exert its influence on the risk of coronary artery disease partially through disturbances of the hemostatic system. The relations of fasting insulin concentrations with the degree of coronary atherosclerosis, other coronary risk factors (including some markers of the insulin resistance syndrome such as body mass index and triglyceride), markers of inflammation, and hemostatic factors were investigated in 1484 patients with angina pectoris. Mean insulin levels were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
174
0
9

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(197 citation statements)
references
References 39 publications
14
174
0
9
Order By: Relevance
“…For that reason, we support again the 10-year-old suggestion by Juhan-Vague et al 27 to definitely accept increased PAI-1 levels as a true component of the metabolic syndrome. The two recent working definitions of the metabolic syndrome 3,4 did not include increased levels of PAI-1 as a criterion for the definition of the metabolic syndrome since they did not find it necessary for the recognition of the condition 3 or because it cannot be identified by routine clinical evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…For that reason, we support again the 10-year-old suggestion by Juhan-Vague et al 27 to definitely accept increased PAI-1 levels as a true component of the metabolic syndrome. The two recent working definitions of the metabolic syndrome 3,4 did not include increased levels of PAI-1 as a criterion for the definition of the metabolic syndrome since they did not find it necessary for the recognition of the condition 3 or because it cannot be identified by routine clinical evaluation.…”
Section: Discussionsupporting
confidence: 89%
“…Relationships between CRP concentrations and fasting insulin levels have been observed in some studies, [11][12][13][14]43,44 and this association has been shown to persist after adjustment for BMI. 14 In the present study, we also found a relationship between CRP concentrations and insulinemia (a crude marker of insulin resistance in nondiabetic subjects), suggesting that hyperinsulinemia resulting from insulin resistance is also associated with a state of low chronic inflammation.…”
Section: Discussionmentioning
confidence: 83%
“…In this regard, our data are consistent with reports relating insulin resistance not only with diabetes, dyslipidemia, hypertension, central obesity and microalbuminuria, but also hyperuricemia, hyperleptinemia, endothelial dysfunction, inflammatory status, thrombophilia, oxidative stress and liver steatosis. [42][43][44][45][46][47][48] In conclusion, the coexistence of multiple metabolic disorders in the single individual, also called Metabolic Syndrome, occurs very frequently in the general population. The syndrome is associated with several nonmetabolic abnormalities documenting thrombophilia, increased oxidative stress, inflammation, endothelial dysfunction, liver steatosis and leptin resistance.…”
Section: Discussionmentioning
confidence: 99%